Pengaruh Pengembangan Manajamen SDM Terhadap Kinerja Karyawan pada Clandys Grosir - Adam Pratama Muhammad Jawas; Andi Amri (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
Clandys Grosir, has a human resource management system plays an important role in improving employee performance. In addition, the human resource management function indicates the extent to which workers are able to complete tasks and have the necessary skills on the fields listed in Clandys Grosir. Respondents at Clandys Grosir Sejahtera numbered thirty people. Quantitative descriptive methods were used in this study to measure the impact of one variable on another. Based on the results of research analysis using IBM SPSS 23, it can be seen that there is a strong relationship between employee performance and human resource development variables. The results of these data include validity and reliability tests, simple linear regression analysis, and hypothesis tests. In addition, the test results of this study show that factors related to human resource development have a positive and significant influence on employee performance.